DOES EDUCATION AND EMPLOYMENT IMPROVE WOMEN’S LIFE EXPECTANCY IN INDONESIA - Muhammad Dzaki Fahd Haekal; Estro Dariatno Sihaloho (Mega Aktiva, 2021)
This paper examine the relation between women’s income, women’s education, and the percentage of women as professional workers toward women’s life expectancy in Indonesia. This research use random effect model with 34 Provinces data from 2010 to 2017. This paper show that women’s income, women’s education, and the percentage of women as professional have positive and significant effect to women’s life expectancy in Indonesia. This paper show that women’s education has bigger effect on women’s life expectancy in Indonesia than women’s income and percentage of women as professional workers.